Differences in Student Performance in Epidemiology Depending on Study Mode. (September 2019) - Mathieu, Erin; Killedar, Anagha; Driscoll, Tim
Studies regarding the effectiveness of online learning compared with that of face to face (F2F) learning are conflicting. Some studies show students studying online have better outcomes, some show they have worse outcomes, and others show there is no difference. This retrospective cohort study compares competence in epidemiological concepts at the end of a graduate unit between Masters of Public Health students who studied F2F and those who studied online. In this unit, F2F students attended a 1-hour lecture (which was recorded) and a 2-hour tutorial each week. Online students listened to the recorded lecture and covered the same tutorial material through a facilitated asynchronous discussion board or a weekly synchronous 2-hour webinar. Students completed the same optional in-semester assignment and end of semester open-book exam. The results from 442 students (55% F2F) who completed the unit between 2015 and 2018 inclusive were included. The analysis compared final unit marks, controlling for prior academic performance. Results indicate that competence was reasonable in both formats of the unit but higher in F2F students, who after adjustment for prior degree academic performance achieved an average of 4.6 (95% confidence interval [2.2, 7.1]) more marks than online students. The better performance for F2F students was particularly true for students with poorer prior academic performance. These results suggest that F2F mode was more effective than online mode, particularly for students with a lower prior academic performance. Course instructors could usefully focus on enhancing student–instructor interaction and targeting students with lower academic ability when delivering online units of study.